Desenvolvimento e avaliação de um aplicativo de comunicação de metas entre cuidadores e profissionais de saúde no tratamento de pessoas com transtorno do espectro autista - Aline Abreu e Andrade (2017)
The proper functioning of a treatment team essentially requires effective communication between all involved. The formation of a large professional network around the patient, faced with complex conditions such as autism spectrum disorder, increases the communication demand necessary to conduct a cohesive and consistent treatment. Therefore, the present study aimed to develop and evaluate a goal communication application among caregivers and health professionals in the treatment of people with autism spectrum disorder. The research was conducted in three stages. Initially, an integrative literature review was carried out on the studies that focused on the theme of team communication in the treatment of children with special needs. The databases PsyArticles (APA), ScienceDirect (Elsevier), Springer, SAGE Journals Online, Oxford Journals and Scielo were used. Eight articles were analyzed and the results indicated a majority of exploratory studies, to the detriment of the propositive researches. Therefore, a study was conducted to develop a communication resource between parents and professionals. It was carried out the identification of facilitating and difficult factors of the use, the elaboration of a test version of the communication tool and a pilot study on its use. The result of the research was the creation of the System of Team Transparency between Parents and Professionals. Using this application, the third stage of the research was carried out, focused on understanding the functioning of the communication between the treatment team of children with ASD and evaluating the possible impacts of introducing a communication and goal reminder application between parents and treatment team. Thirty treatment teams participated in the study, that was conducted with a longitudinal design. The results suggest an increase in the communication of the caregivers with the professionals after the period of use of the application. We also identified an association between the frequency of use of the application by professionals and the satisfaction of caregivers with the resource. However, the results point to a low frequency of communication within the teams, as well as users' difficulties in adhering to the application. In view of this, it is necessary to carry out new studies that continue the issues raised on the theme of team communication.